Genome‐wide association for protective variants in Alzheimer's disease in the Midwestern Amish. (December 2021) - Main, Leighanne R; Song, Yeunjoo E.; Laux, Renee A.; Miskimen, Kristy L.; Cuccaro, Michael L.; Ogrocki, Paula K.; Lerner, Alan J.; Vance, Jeffery M.; Fuzzell, M. Denise; Fuzzell, Sarada L.; Sewell, Jane L.; Caywood, Laura J.; et al.
Abstract: Background: Alzheimer's disease (AD) is a progressive neurological disease that leads to atrophy of the brain and cognitive decline. There are many factors that play a role in the risk of AD, such as age, smoking, gender, and genetics. the genetic influence on AD is strong, with heritability estimates between 40‐60%. Identifying genetic factors that either increase or decrease AD risk are critical in the understanding of this disease. Here, we studied a homogeneous, isolated population – the Ohio and Indiana Amish – to identify protective genetic factors for AD. Our previous studies in the Amish documented numerous individuals who are cognitively normal at advanced ages. Method: Here, we have completed a genome wide association study (GWAS) on Amish individuals who are at high risk for AD (i.e., have an affected sibling and are over 76 years of age), but are cognitively normal. We have genotypes on 2096 individuals, 921 of which are being analyzed for association, in which we have a complex 5, 000‐person, 13‐generation pedigree to help inform our results. MEGAex and GSA chips were used for genotyping. Both KING and GENESIS software were used for quality control and association analyses since they control for both population structure and kinship in evaluating association via a generalized linear mixed model (GLMM). Result: We included 601 cognitively normal (CN), 320 cognitively impaired (CI) individuals. Association analysis was done on a total of 921 individuals, with 256, 978 SNPs. We had a total of four SNPs reach a significance threshold of p ≤ 5 x 10 ‐5 to also include suggestive association loci in our examination. (Nearest genes: DISC1, IQGAP2, and LOC401478 on chromosomes 1, 5 and 8. One SNP on chromosome 13, rs1556774, has no gene association currently known, and no known gene within 80kb.) These loci are currently under further examination. Conclusion: We studied cognitively resilient individuals from a founder population to identify potential protective genetic variants for AD. We identified four SNPs associated with CN in at‐risk adults over 75. These loci might influence cognitive resilience. Here we have shed some light on possible genetic factors that may contribute to protection from cognitive decline.